2012
DOI: 10.1152/ajprenal.00385.2011
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying the inhibitory effects of uroguanylin on NHE3 transport activity in renal proximal tubule

Abstract: -We previously demonstrated that uroguanylin (UGN) significantly inhibits Na ϩ /H ϩ exchanger (NHE)3-mediated bicarbonate reabsorption. In the present study, we aimed to elucidate the molecular mechanisms underlying the action of UGN on NHE3 in rat renal proximal tubules and in a proximal tubule cell line (LLC-PK1). The in vivo studies were performed by the stationary microperfusion technique, in which we measured H ϩ secretion in rat renal proximal segments, through a H ϩ -sensitive microelectrode. UGN (1 M) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…Previous studies have shown that the natriuretic peptide uroguanylin, which activates the guanylate cyclase C receptor/cGMP pathway, also inhibits NHE3 activity by increasing NHE3 phosphorylation at both the 552 and 605 PKA consensus sites and by decreasing the surface expression of NHE3 in proximal tubule cells (Lessa et al . ). Protein phosphatases are targets of NO (Pfeilschifter et al .…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that the natriuretic peptide uroguanylin, which activates the guanylate cyclase C receptor/cGMP pathway, also inhibits NHE3 activity by increasing NHE3 phosphorylation at both the 552 and 605 PKA consensus sites and by decreasing the surface expression of NHE3 in proximal tubule cells (Lessa et al . ). Protein phosphatases are targets of NO (Pfeilschifter et al .…”
Section: Discussionmentioning
confidence: 97%
“…Fonteles et al (68) have demonstrated that chronic ingestion of NaCl for 10 days, at a concentration of 2% in drinking water, causes the kidney tissues to respond to a sub-threshold uroguanylin dose during ex vivo renal perfusion, suggesting a sensitization of kidney receptors to this hormone. In a very recent publication, Lessa et al (69) showed that uroguanylin reduces sodium-proton transport activity (NHE 3 ) in rat renal proximal tubules in a mechanism mediated by both cGMP/PK6 and cAMP/PKA signaling pathways with a parallel reduction in NHE 3 surface expression (Figure 2B). Baba et al (70) demonstrated that uroguanylin, at concentrations that have no effect on normal rats, significantly increases urinary sodium excretion in nephrotic rats, which could be important when treating clinical conditions involving sodium retention.…”
Section: Gastrointestinal and Kidney Hydrosaline Balance Is Influencementioning
confidence: 98%
“…It was initially proposed that the dietary ingestion of salt induces an increase in the secretion of proUGN by EC . proUGN is converted to UGN in the intestine and the renal tubules , leading to an increase of Na + in the urine (Greenberg et al 1997, Nakazato et al 1998, Lessa et al 2012) and a decrease in intestinal Na + absorption (Joo et al 1998, Toriano et al 2011. As part of this entero-renal axis, UGN signaling acts by regulating Na + homeostasis.…”
Section: Other Functions Of Ugnmentioning
confidence: 99%